Death by a thousand sips - Rue, Gretchen (Rue, Gretchen. Witches' Brew mystery, 2023)
"Ever since she moved to Raven Creek, Washington, Phoebe Winchester knew she would have to grow accustomed to having a lot on her plate. She's beginning to make the Victorian manor she inherited from her dear and adventurous Aunt Eudora feel more like home, successfully running the bookstore and tea shop, The Earl's Study, and learning to harness her recently discovered magical powers. But when she discovers a dead body at an estate sale--even Phoebe wonders if this is simply too much. Rumors of Phoebe's involvement force her to take action; she needs to find the killer and clear her own name, once again. She enlists Rich Lofting, the handsome private detective and her childhood friend, in her investigation, all while she sorts out her unresolved feelings for him. Is there something more sinister lurking in the shadows of this small tight-knit town? And does Phoebe really want to find out? With a dash of magic, a pinch of sleuthing skills, and a spoonful of friendly assistance, Phoebe needs to uncover the killer to keep Raven Creek safe once again. But if she doesn't--will she find herself in even more hot water?"--